Manajemen risiko operasional dan reputasi dalam implementasi Fintech pada Bank Syariah di era digital - Fauziyah, Tatia Nur (Maliki Interdisciplinary Journal, 2026)
The development of financial technology (fintech) has driven significant transformation in the Islamic banking industry in the digital era, especially in improving service efficiency, accessibility, and competitiveness. However, fintech implementation also raises various increasingly complex risks, especially operational and reputational risks. This study aims to analyze operational risk management and reputation in the implementation of fintech in Islamic banks and identify the challenges faced in their management. The method used is a qualitative approach with literature studies on various relevant scientific sources. The results show that operational risks arise due to technological system failures and human error, while reputation risks are closely related to customer trust, data security, and compliance with sharia principles. In addition, a risk management system that still tends to be conventional is an obstacle in dealing with digital-based risk dynamics. Therefore, it is necessary to strengthen adaptive, integrated, and technology-based risk management, as well as increase the role of Islamic supervision to maintain the stability and reputation of Islamic banking in the digital era.